Two cytotoxic squalene-derived polyethers from the Japanese red alga Chondria armata. Issue 23 (2nd December 2021) - Hamada, Toshiyuki; Kobayashi, Kazushi; Arima, Naomichi; Tani, Fumito; Vairappan, Charles Santhanaraju; Onitsuka, Satoaki; Okamura, Hiroaki
Abstract: The red alga Chondria armata is known to produce and contain a rich diversity of secondary metabolites, such as domoic acid-related alkaloids and triterpene polyethers. Our investigation on red alga C. armata from Kagoshima coast, Japan, resulted in the isolation of two new triterpene polyethers, bandokorols A (1 ) and B (2 ). The structures of these compounds were determined based on spectroscopic data such as infrared (FTIR), 1 H-NMR, APT, 1 H– 1 H-COSY, HSQC, HMBC, NOESY and FAB mass spectrometry (HRFABMS). The anticancer potentials of these compounds were tested against adult T-cell leukaemia (ATL), S1T cells and their IC50 values are reported here. Graphical Abstract: